Justice Delivered Locally : Systems, Challenges, and Innovations in Solomon Islands - Allen, Matthew; Dinnen, Sinclair; Evans, Daniel; Monson, Rebecca (World Bank, Washington, DC, 2014)
This report presents the research findings of the Justice Delivered Locally (JDL) initiative of Solomon Islands' Ministry of Justice and Legal Affairs, which was supported by the World Bank's Justice for the Poor (J4P) program. JDL supports the Solomon Islands Government (SIG) policy of reinvigorating local-level justice systems. This is based on an understanding that developmentally important local governance and conflict management capacities (both state and non-state) have been significantly weakened since 1978, the post-independence era, and were not rebuilt even after the period of violent conflict and social disorder known as the 'tension' (1998-2003). Overall, the research indicates that rural citizens by and large prefer to use locally based, non-state systems to address disputes. These local non-state systems, where functioning, are generally seen as culturally relevant, responsive to local needs, accessible, and well understood. However, these local kastom systems, typically associated with 'traditional' authority exercised by chiefs, are under immense stress owing to larger processes of change and newer types of conflict. While there is considerable geographical variation, in some places local systems have broken down altogether. This is due in part to the entanglement of chiefs and local leaders in parochial and self-interested power struggles, especially in the context of natural resource development, particularly logging. This paper is the fourth in a series that has been produced under the JDL initiative. Forthcoming is a fiscal and institutional analysis of local courts, customary land appeal courts, and magistrates' courts, and a final note synthesizing policy recommendations from all of these components. While this work was undertaken under the purview of the Ministry of Justice and Legal Affairs, the findings and analysis presented herein represent the views of the JDL researchers and do not necessarily reflect the views of the SIG.